2004
DOI: 10.1161/01.cir.0000131940.19833.85
|View full text |Cite
|
Sign up to set email alerts
|

Intra-Arrest Cooling Improves Outcomes in a Murine Cardiac Arrest Model

Abstract: Background-Recent clinical studies have demonstrated that hypothermia to 32°to 34°C provides significant clinical benefit when induced after resuscitation from cardiac arrest. However, cooling during the postresuscitation period was slow, requiring 4 to 8 hours to achieve target temperatures after return of spontaneous circulation (ROSC). Whether more rapid cooling would further improve survival remains unclear. We sought to determine whether cooling during cardiac arrest before ROSC (ie, "intra-arrest" hypoth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
235
2
9

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 342 publications
(251 citation statements)
references
References 22 publications
(20 reference statements)
5
235
2
9
Order By: Relevance
“…The neurologic outcomes of the studied animals were evaluated with neurologic function scoring at the sixth, 24th, 48th, and 72nd hours following ROSC (Table 1). 19 Assessments were performed independently by two investigators. Any discrepancies were resolved by an independent assessment by a third investigator, and the score chosen by the majority was accepted.…”
Section: Study Protocolmentioning
confidence: 99%
“…The neurologic outcomes of the studied animals were evaluated with neurologic function scoring at the sixth, 24th, 48th, and 72nd hours following ROSC (Table 1). 19 Assessments were performed independently by two investigators. Any discrepancies were resolved by an independent assessment by a third investigator, and the score chosen by the majority was accepted.…”
Section: Study Protocolmentioning
confidence: 99%
“…However, the optimal timing and duration of hypothermia after arrest with respect to reperfusion remains unclear, with the suggestion that "sooner is better" in terms of cooling onset relative to reperfusion (31a). Indeed, cooling in our mouse model of cardiac arrest is highly protective against cardiac and neurological injury when induced during ischemia (i.e., during cardiac arrest) and maintained for 1 h after reperfusion (i.e., ROSC) (1). Delaying hypothermia by even minutes into reperfusion after cardiac arrest abrogates protection (1).…”
mentioning
confidence: 95%
“…The intravenous administration of potassium chloride was also shown to induce a very reproducible cardiac arrest in rodents [9,13,14]. It leads to a quasi-immediate cardiac arrest with asystole.…”
Section: Asystole Through Potassium Chloride Administrationmentioning
confidence: 96%
“…On the other hand, spontaneous heart rate is much higher in rodents than in large animals and humans as usual values average 260-450 or 500-600 beats per minute in awake rats and mice, respectively [7,8]. This directly impacts the required chest compression rate in those species as mice should undergo ≈400 compressions per min to be resuscitated [9][10][11][12][13][14]. Magnetic resonance imaging also showed that usual ejection fraction are higher in mice as compared to humans (75% vs 55%) [15].…”
Section: Cardiac Arrest In Rodentsmentioning
confidence: 99%
See 1 more Smart Citation